Peran Lingkungan Kerja Fisik Dan Nonfisik Dalam Mendukung Produktivitas Pegawai Kelurahan Di Kota Baubau - Husnah Katjina; Hasni (Jurnal Multidisipliner Bharasumba, 2026)
This study examines the role of the work environment in supporting employee productivity at the Kadolomoko Urban Village Office, Kokalukuna District, Baubau City. A qualitative approach was employed, with data collected through observation, interviews, and documentation. Three informants representing leadership and staff participated in the study. The findings indicate that the physical work environment is generally supportive, as reflected in the availability of office space, equipment, lighting, ventilation, air conditioning, Wi-Fi, prayer and rest rooms, and CCTV. The non-physical environment is also favorable, characterized by harmonious communication, teamwork, and supportive relationships between leaders and employees. These conditions contribute to work quality, timely task completion, employee morale, and discipline. However, the limited parking area remains a notable constraint. Therefore, improved parking management and continuous maintenance of workplace facilities are recommended to sustain employee comfort and productivity.